Tailoring the Morphological Properties of PVA Nanofibrous Mats by Manipulating Working Planes - Hayriye Hale Aygün (Journal of Nanotechnology)
Despite the process, solution, and ambient parameters of the electrospinning technique have been intensely studied, the effects of different setup orientations have not been thoroughly investigated. In many research studies, the attempts on electrospinning of polyvinyl alcohol have been performed with a horizontal electrospinning or researchers have not even mentioned the setup orientation. This paper examines the morphological properties of polyvinyl alcohol-based fibrous mats electrospun with the same apparatus and identical process and solution parameters but with different working planes, namely, (x)-axis, (+y) axis, and (−y) axis. From the test results, it is concluded that the (−y) axis is the most versatile working plane because fibrous mats have the finest nanofiber diameters with the lowest diameter variation, the medium-level pore area with the smallest pore sizes. Besides, the highest packing density and highly deposited structure with the longest fibers with a high aspect ratio are constructed in this setup orientation. (−y) axis electrospinning is more favorable than that of other working planes for polyvinyl alcohol-based permeable membranes and biostructures.